Paint and decay: A colloquial conversation on preserving the urban heritage - Diandra Pandu Saginatari; Adrian Perkasa (Department of Architecture Faculty of Engineering Universitas Indonesia, 2021)
This paper is an attempt to converse about urban heritage preservation and its experience. To converse is to colloquially discuss ideas that comes to mind while we are looking back at the 2019 photographs of some parts of Kota Tua Surabaya (The Old Town of Surabaya) and reflect upon our knowledge background, one of architecture, the other of history. This conversation is created through a form of creative writing, creative nonfiction, where we begin with our personal thoughts, one of experiencing ruination and the other of witnessing complexity of urban heritage preservation, one of decay and the other of paint. We involve relevant discourses and the use of visual materials such as collages, diagrams, and drawings as a form of visual inquiry and visual illustration, showing the interpretation, reality, and the imagination of fragments of Kota Tua Surabaya. The process involved in creating this conversation could be one of the ways to creatively build collaborative knowledge and have the writings and the visual materials based on personal voice, expanding the academic form of writings.